Long-term clinical outcomes for patients with uncrossable patent foramen ovale - Shin, Yonghoon; Jang, Albert Youngwoo; Won, Yoonsun; Yang, Taeil; Kim, Joohan; Lee, Joonpyo; Seo, Jeongduk; Kim, Minsu; Oh, Pyung Chun; Chung, Wook-Jin; Moon, Jeonggeun; Kang, Woong Chol (Frontiers in Cardiovascular Medicine, 2023)
Introduction Patent foramen ovale (PFO) closure is performed in selected patients with cryptogenic stroke to prevent recurrence. The prognosis of patients with uncrossable PFO after failed guidewire or catheter passage during the procedure remains unknown. We compared the long-term prognosis between uncrossable PFO and successful PFO closure in patients with high-grade PFO shunts. Methods We analyzed patients who underwent PFO closure for stroke or transient ischemic attack (TIA) prevention at Gachon University Gil Medical Center between April 2010 and March 2022. The primary outcome was a composite of recurrent stroke or TIA. Secondary outcomes included stroke, TIA, all-cause death, and a composite of stroke, TIA, and all-cause death. Results Of 286 patients, 245 were included in the analysis after excluding those with transseptal puncture technique usage or concurrent atrial septal defect. Among them, 82 had uncrossable PFO, and 163 underwent successful PFO closure. Large shunts were more prevalent in the PFO closure group compared to the uncrossable PFO group (62.0% vs. 34.1%, P < 0.001), and resting shunts were also more common in the PFO closure group (17.8% vs. 2.4%, P < 0.001). Stroke or TIA occurred in 2 patients (2.4%) in the uncrossable PFO group and 8 patients (4.9%) in the PFO closure group (hazard ratio, 1.44; 95% confidence interval, 0.30–6.81; P = 0.647). Additionally, no disparities in the occurrence of stroke or TIA were found in subgroups divided by baseline characteristics, RoPE score, or shunt grade. Conclusion Clinical outcomes for patients with uncrossable PFO seem similar to those with successful PFO closure.